Adapting an Osteoarthritis Peer Mentorship Intervention for Remote Delivery to People Experiencing Socioeconomic Disadvantage: A Multi‐Method Approach - Anna M. Anderson; Elizabeth Lavender; Samantha Mason; Linda Eckersley; Susan Barry; Amrit Daffu‐O'Reilly; Heidi Green; Mark Conner; Gretl A. McHugh (Health Expectations)
ABSTRACT Background Osteoarthritis (OA) is a common musculoskeletal condition which can cause debilitating pain and other symptoms. OA is more prevalent, and the impact is greater, among people experiencing socioeconomic disadvantage. While peer support is a recommended strategy for addressing these health inequalities, evidence in this area is limited. We previously developed and feasibility tested an in‐person OA peer mentorship intervention in a group with limited diversity. This study adapted the intervention for remote delivery to people experiencing socioeconomic disadvantage. Methods This multi‐method study was informed by the ADAPT guidance. Focus groups and interviews were conducted with 20 adults with hip/knee OA experiencing socioeconomic disadvantage to explore barriers and enablers to engagement with remote OA peer mentorship. The findings and project team members' suggestions informed provisional adaptations. The intervention was further adapted and finalised through two participatory workshops conducted with five people with relevant lived experience, four community organisation representatives, and six Patient and Public Involvement (PPI) representatives; and four intervention delivery practice runs undertaken by four PPI representatives. Findings A wide range of barriers and enablers were identified to two target behaviours – using self‐management strategies and attending remote OA peer mentorship sessions. The identified barriers/enablers and additional study activities led to various adaptations. These spanned the delivery and content of the peer mentor training, mentorship sessions, and supporting resources. The adapted intervention consists of six 1‐h self‐management support sessions delivered remotely by a trained peer mentor. The remote format is flexible, with support available for addressing barriers related to making videoconferencing calls. Conclusions This study rigorously and systematically adapted an in‐person OA peer mentorship intervention for remote delivery to people experiencing socioeconomic disadvantage. Employing a multi‐method approach with diverse partners was key to identifying what adaptations were required. Patient or Public Contribution PPI representatives played a central role in this study as project team members (two individuals), Project Advisory Group members (three individuals), and wider PPI group members (six additional individuals). This extensive PPI aimed to ensure the adapted OA peer mentorship intervention is useful, acceptable, and accessible to the people it aims to benefit. Trial Registration ISRCTN registration of the overall project was obtained on 18 May 2023 (ISRCTN78088278).